Olam significantly reduces food loss and greenhouse gas emissions: 14% of total emissions (117 kton CO2eq for Nigerian farmers supplying to Olam) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Olam used CCAFS-WFBR science (hotspot analysis + ACE calculator) to identify threshing and harvesting as hotspots for food loss and waste and greenhouse gas emissions and quantify benefits of interventions.